Halfway to Nowhere: Migration as Exclusion in the Comic Book "Freda" - Miranda-Barreiro, David (Madrygal. Revista de Estudios Gallegos, 2024)
The comic book Freda (2002) by Kike Benlloch and Alberto Vázquez tells the story of a Galician family that emigrated to Central Europe during the mid-1950s. The exact location of the story is ambiguous, as it is a German speaking country which could be either Germany or Switzerland. Forced to leave due to the lack of work in Galicia, the parents become part of the group of migrants who, via the Instituto Nacional de Emigración (National Institute of Emigration), were exploited in the destination countries. While his parents show little interest in integrating into the new society, since they see their stay as temporary, their son Manu (who arrives at the age of ten) begins to establish emotional ties with the host culture. Especially thanks to the help of his friend Freda, with whom he will later have a sentimental relationship, Manu will feel that his home is no longer in Galicia but where her girlfriend is. Six years later, back in Galicia due to the physical problems caused by the hard work on his father’s health, it is Manuel who is unable to readapt. Drawing on a multidisciplinary theoretical framework (migration studies, affect theory, gender studies and comics studies), this article analyses the representation of the consequences that the migratory policy of the dictatorship had on the mental and emotional health of the migrants. It proposes to examine Manu as a figure of exclusion, who ends up “halfway” (in his own words), not fully belonging to anywhere.